Safety and efficacy of a freeze-dried trivalent antivenom for snakebites in the Brazilian Amazon: An open randomized controlled phase IIb clinical trial. - Iran Mendonça-; Antônio Magela Tavares; Jacqueline Sachett; José Felipe Sardinha; Lilian Zaparolli; Maria Fátima Gomes Santos; Marcus Lacerda; Wuelton Marcelo Monteiro (Public Library of Science (PLoS), 2017)
In tropical areas, a major concern regarding snakebites treatment effectiveness relates to the failure in liquid antivenom (AV) distribution due to the lack of an adequate cold chain in remote areas. To minimize this problem, freeze-drying has been suggested to improve AV stability.This study compares the safety and efficacy of a freeze-dried trivalent antivenom (FDTAV) and the standard liquid AV provided by the Brazilian Ministry of Health (SLAV) to treat Bothrops, Lachesis and Crotalus snakebites. This was a prospective, randomized, open, phase IIb trial, carried out from June 2005 to May 2008 in the Brazilian Amazon. Primary efficacy endpoints were the suppression of clinical manifestations and return of hemostasis and renal function markers to normal ranges within the first 24 hours of follow-up. Primary safety endpoint was the presence of early adverse reactions (EAR) in the first 24 hours after treatment. FDTAV thermal stability was determined by estimating AV potency over one year at 56°C. Of the patients recruited, 65 and 51 were assigned to FDTAV and SLAV groups, respectively. Only mild EARs were reported, and they were not different between groups. There were no differences in fibrinogen (p = 0.911) and clotting time (p = 0.982) recovery between FDTAV and SLAV treated groups for Bothrops snakebites. For Lachesis and Crotalus snakebites, coagulation parameters and creatine phosphokinase presented normal values 24 hours after AV therapy for both antivenoms.Since promising results were observed for efficacy, safety and thermal stability, our results indicate that FDTAV is suitable for a larger phase III trial.ISRCTNregistry: ISRCTN12845255; DOI: 10.1186/ISRCTN12845255 (http://www.isrctn.com/ISRCTN12845255).